Associação dos genes KIR e seus ligantes HLA com o desenvolvimento da cardiopatia chagásica crônica em uma população da região Norte/Noroeste do Paraná - Ayo, Christiane Maria (2012)
Chagas disease, caused by Trypanosoma cruzi, occurs throughout Latin America and affects millions of people. The disease is classified in its acute and chronic phase but the clinical manifestations vary from one endemic area to another and this variation can be attributed to genetic factors. KIR genes (killer cell immunoglobulin-like receptor) encode the molecules that activate and inhibit the function of molecules of NK cells (natural killer) and have as ligands HLA (human leukocyte antigen) class I. Both KIR and HLA molecules are highly polymorphic and the specific KIR-HLA allelic combinations may regulate NKcell-mediated immunity against infectious pathogens. The purpose of this study was to investigate the influence of KIR genes and their HLA ligands in the development of chronic Chagas heart disease. The participants in this research include 124 patients serologically diagnosed with Chagas disease (57 men and 67 women, with a mean age of 60,2 years ±9,9) who were seen at the University Hospital of Londrina and the Chagas Disease Lab of the State University of Maringá. We also had 163 healthy individuals, spouses of patients or blood donors of the Regional Blood Center of Maringa (94 men and 69 women, with a mean age of 49,3 years ±6,1). Genotyping of KIR genes and allelic groups of HLA was performed using the PCR-SSOP. The observed gene frequencies were determined by direct counting and statistical analysis was performed using the Fisher exact test and Chi Squares with Yates correction. The pair KIR2DL2-C1/C2 (16.1% vs 29.4% P=0.012,OR=0.46,CI=0.24-0.85) and KIR3DL2-A3/11 (20.6% vs 31.9%, P=0.035,OR=0.53,CI=0.29-0.96) were less frequent in patients. KIR activator and its ligands, such as the combination KIR2DS2+/2DL2-/C1+ was more frequent in patients (11.3% vs 4.3%, P=0.042,OR=2.83,CI=1.02-1.55 ) and in patients with cardiac involvement (17.1% vs 4.3%, P=0.001,OR=4.58,CI=1.26-16.3) compared to controls. The combination KIR2DS2+/2DL2-/KIR2DL3+/C1+ was also positively associated with Chagas disease (10.5% vs 6.7%, P=0.039,OR=3.06,CI=1.13-8.30) and chronic chagasic cardiopathy (14.6% vs 3.7%, P=0.021,OR=4.48,CI=1.36-14.73). Thus, NK cells contribute to tissue lesion in chronic chagasiccardiopathy .